The Responses of Germ-Free Zebrafish (Danio rerio) to Varying Bacterial Concentrations, Colonization Time Points, and Exposure Duration - Tan, Fang; Limbu, Samwel Mchele; Qian, Ye; Qiao, Fang; Du, Zhen-Yu; Zhang, Meiling (Frontiers in Microbiology, 2019)
Colonizing germ-free (GF) zebrafish with specific bacterial species provides the possibility of understanding the functions of bacteria in a simpler environment. However, the responses of GF zebrafish to various colonization conditions such as bacterial concentrations, colonization time points and exposure duration remain unclear. To address this issue, we explored the responses of GF zebrafish by using two bacterial species at varying concentrations, colonization time points and exposure duration. We mono-associated GF zebrafish with Escherichia coli DH5α or Bacillus subtilis WB800N at concentrations ranging from 102 to 107 CFU/ml either at 3 day post fertilization (dpf) or 5 dpf for 24 or 48 hr. We evaluated the responses of GF zebrafish by analyzing the survival rate, colonization efficiency, nutrients metabolism, intestinal cell proliferation, innate immunity, stress responses and behavior response by comparing it to conventionally raised zebrafish (CONR) and GF zebrafish. The results indicated that the final bacteria concentrations ranging from 102 to 104 CFU/ml did not cause any mortality when GF mono-associated larvae were exposed to either E. coli DH5α or B. subtilis WB800N at 3 dpf or 5 dpf, while concentrations from 106 to 107 CFU/ml increased the mortality particularly for 5 dpf. The E. coli DH5α mainly induced the expression of genes related to nutrients metabolism and cell proliferation while B. subtilis WB800N mainly upregulated the expression of genes related to innate immunity or stress responses. Moreover, our data revealed that GF zebrafish showed higher levels of physical activity than CONR and the microbial colonization reduced the hyperactivity of GF zebrafish, suggesting colonization of bacteria affected behavior characteristics. This study provides useful information on bacterial colonization in GF zebrafish for microbiota future studies.